2012
DOI: 10.4172/2155-9546.1000147
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of Nile Tilapia, Oreochromis niloticus, by Nigella sativa and Bacillus subtilis

Abstract: The aim of this study is to investigate the modulation of the immune system of Nile tilapia, Oreochromis niloticus, by the black cumin seeds, Nigella sativa, or Bacillus subtilis PB6 (CloSTAT) as feed additives. Four diet regimes, a basic (control), CloSTAT, nigella, or combination of the black cumin seeds and CloSTAT were formulated and used to feed fish for 30 successive days. Half of the fish were used to investigate some of the immune parameters as serum globulins, white blood cell counts, and phagocytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Similarly, diets with 1%, 2% and 3% NSO fed for 14 days enhanced the immune response (lysozyme, antiprotease, total protein, myeloperoxidase, bactericidal activity and IgM titres) of rainbow trout (Awad, Austin & Lyndon 2013). It has been reported that feeding Nile tilapia with 3% NSS for 30 successive days significantly increased white blood cell counts and significantly decreased the mortality rate when fish were challenged with A. hydrophila compared to those that received the control diet (Elkamel & Mosaad 2012). However, our in vitro preliminary screenings did not detect an inhibitory effect for NSO against A. hydrophila isolates.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, diets with 1%, 2% and 3% NSO fed for 14 days enhanced the immune response (lysozyme, antiprotease, total protein, myeloperoxidase, bactericidal activity and IgM titres) of rainbow trout (Awad, Austin & Lyndon 2013). It has been reported that feeding Nile tilapia with 3% NSS for 30 successive days significantly increased white blood cell counts and significantly decreased the mortality rate when fish were challenged with A. hydrophila compared to those that received the control diet (Elkamel & Mosaad 2012). However, our in vitro preliminary screenings did not detect an inhibitory effect for NSO against A. hydrophila isolates.…”
Section: Discussionmentioning
confidence: 96%
“…346-354) antistress [41] (pp. [19][20][21][22][23][24][25] and antioxidants [42] (pp. 277-284) in aquaculture practices.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of dietary black seed have been shown on the growth performance, biochemical and immuno-haematological parameters of Carrasius auratus [22] (pp. 285-290), Oreochromis niloticus [23] (pp. 1-4), Lates calcarifer [24] (pp.…”
Section: Introductionmentioning
confidence: 99%